DEPENDENCE OF NEUROPSYCHOLOGICAL DEVELOPMENT OF EARLY AGE CHILDREN FROM THE FUNCTIONAL ACTIVITY OF SEROTONERGIC AND PITUITARY-THYROID SYSTEMS - Shlieienkova, H. O. (The Journal of V. N. Karazin Kharkiv National University, series "Medicine")
The high frequency of neurological disorders in children deprived of parental care was demonstrated (94.1 ± 2.2 %). The most commonly the syndrome of statokinetic, mental and pre-speaking retardation was diagnosed (49,2 ± 4,7 %, p < 0,001). High frequency disturbances of mental development and neurological status are accompanied by a reduction in the functional activity of the pituitary-thyroid system and the activation of serotonin. Between levels of thyrotropin and serotonin in the blood serum there is a moderate direct correlation (ρ = 0,56), which may indicate the adaptive increasing of the serotonin system activity, designed to compensate the lack of thyroid effects.